Caronary Artery Disease in Women - Neki, NS (Journal of Medicine, 2014)
Coronary artery disease (CAD) - which includes coronary atherosclerotic disease, myocardial infarction (MI), acute coronary syndrome and angina - is the most prevalent form of cardiovascular disease and is the largest subset of this mortality. Coronary artery disease (CAD) is a leading cause of death of women and men worldwide. CADs impact on women traditionally has been underappreciated due to higher rates at younger ages in men. Microvascular coronary disease disproportionately affects women. Women have unique risk factors for CAD, including those related to pregnancy and autoimmune disease. DOI: http://dx.doi.org/10.3329/jom.v15i2.20687 J MEDICINE 2014; 15 : 135-140